Short-Term Clinical and Radiographic Outcome after Stabilization of Femoral Capital Physeal Fractures with Cortical Positional Screws in 39 Cats - Vink, Joris Johannes Wilhelmus Gerardus; Hubers, Mike Willem Laurens; den Hertog, Erik; Schaeffer, Ingrid Geraldine Fernanda; van Zuilen, Dick; Maarschalkerweerd, Roelof Jozef; van Klaveren, Nicolien Jacoba (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The aim of this study was to report the short-term clinical and radiographic outcome for the treatment of femoral capital physeal fractures with cortical positional screws in cats.Study Design Medical records and radiographs of cats with femoral capital physeal fractures stabilized with cortical positional screws were retrospectively reviewed. Signalment, bodyweight, femoral head affected, fracture classification, fracture reduction, implants, concurrent orthopaedic injuries, osteoarthritis, femoral neck osteolysis, complications and 6-week follow-up clinical results were recorded. A short- to long-term follow-up was performed by telephone questionnaire with the owners.Results Forty-six fractures in 39 cats met the inclusion criteria. In 45/46 fractures, radiographic signs of bone healing were present and 35/39 cats were assessed as walking normally by a veterinarian at 6-week follow-up. There was a significant increase in radiographic signs of osteoarthritis (p=0.037) and femoral neck osteolysis (p=0.001) on 6-week follow-up radiographs. Pre- and postoperative osteoarthritis and femoral neck osteolysis were not associated with clinical outcome. The mean follow-up period for the telephone questionnaire was 48 months (range, 5–147 months). Seven out of 25 owners reported a gait abnormality in the short- to long-term.Conclusion Femoral capital physeal fractures in cats can be treated successfully with the use of cortical positional screws. This technique may be considered as an alternative to other primary fixation techniques and salvage procedures for the treatment of femoral capital physeal injuries in cats. This technique seemed successful in cats with a low-grade preoperative femoral neck osteolysis.
Keywords: femoral capital physeal fracture; screw fixation; osteolysis; cats